Policy Coordination and Outcomes: Theoretical Perspectives and Empirical Evidence in Nigeria - Adewale, ADEGBOYE Abiodun (Journal of Economics and Behavioral Studies, 2020)
The paper discusses the fiscal-monetary coordination and the resultant outcomes in macroeconomic aggregates from theoretical and empirical perspectives. The game-theoretic technique was also used to analyse the policy mix conundrum vis-a-vis the fiscal-monetary policies interaction and how that translates into optimal outcomes in an economy. However, the situation of making or forcing monetary policy to be subordinate to fiscal policy may still not generate socially optimal results. This is not far-fetched as the payoffs in the game-theoretic model suggest the presence of minimal coordination problem but high policy conflict even if both authorities are disciplined. Coordination problem and goal conflict seem to be non-existent - when both fiscal and monetary policy blocks are committed and responsible in their choices. Further analyses indicate that the policy mix of both fiscal and monetary authorities for inflation seemed complementary. Inflation responded negatively to the shock of debt in the short run. However, in the medium term, the shock becomes positive and later returns to the initial state. The study suggests that policy designs in Nigeria must harmonise both stabilisation and growth objectives to have optimal outcomes.